Trade and Migration: Firm-Level Evidence (LONG VERSION) - Andreas Hatzigeorgiou; Magnus Lodefalk (Örebro University School of Business, 2011)
Migration has been associated with higher levels of trade. Previous studies interpret this as evidence of migrants' ability to lower trade costs. Nevertheless, no study has investigated the impact of migrants on firms' foreign trade. Thus, they fail to both provide evidence on the role that migrants may play in lowering firms' trade costs, and exactly through which mechanisms the impact is derived. This study, being the first to study in depth the impact of immigration on trade at the firm level, bridges this gap in research. It utilizes new and unique employer-employee data for 12,000 Swedish firms, for the period 1998-2007, in a firm-level gravity framework. It provides novel firm-level evidence, demonstrating a significant, positive, and robust impact of immigrants in raising firms' foreign trade. Migrants are found to increase trade both on the extensive and intensive product margin. Further, the study is able to conclude that the sustained effect mainly derives from lower information frictions through superior knowledge of foreign-markets, although contacts are also important.
Keywords: D22; D83; F14; F22; 330; trade costs; information; trust; migration; heterogeneous firms; gravity; firmlevel data; product margins